Design and Development of Water Pump Controlling and Monitoring Tools Based on the Internet of Things - Rahayu, I Made Pastika; Piarsa, I Nyoman; Cahyawan Wiranatha, A.A.K. Agung (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2023)
Water in the reservoir on the first floor is often empty, resulting in no running water for each toilet in the Information Technology. In addition, the water pump in the Information Technology is still turned on manually, so the officer must occasionally control the water pump. Method Software Development Life Cycle (SDLC) Waterfall model to be used in this study. The hardware used is NodeMCU ESP8266, HCS-R04 which functions to measure water level and water volume, relay, and YF-B10 which functions to measure water discharge and volume. The results obtained were that the water level measured using the HCS-R04 was 11 cm high, while the water level was 10.7 cm measured using a meter. The water discharge obtained is 6 L/m. The water pump status feature, and the ON/OFF feature on the Android application are declared successful for turning on and turning off the water pump.